Fenomena Pelecehan Seksual Area Kampus Universitas Jember - Maris Jennet Landicho; Frisca Putri; Ajeng Cahya (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Sexual harassment is an unexpected and unwanted action, but the rise of sexual harassment in society cannot be covered up starting from verbal and nonverbal actions. This research is a type of descriptive qualitative research that uses qualitative research methods and uses a phenomenological approach. We can know that the perpetrators of sexual harassment are dominated by men, but it is unfortunate that even though this sexual harassment has been widely known by the wider community and the authorities still cannot take serious attention or take legal action quickly.